Societal costs of primary progressive multiple sclerosis in Australia and the economic impact of a hypothetical disease-modifying treatment that could delay disease progression. (1st January 2021) - Brown, Laurie J.; Li, Jinjing; Brunner, Matthias; Snoke, Martin; La, Hai A.
Abstract: Aims: Primary progressive multiple sclerosis (PPMS) has a progressive course of disability with continuous neurological worsening. We investigated societal costs of PPMS in Australia and the economic impact of increasing the independence of people with PPMS through delaying disease progression. Methods: This prevalence-based retrospective cost-of-illness analysis used observational data from publicly available secondary data sources and literature findings. Direct and indirect costs of PPMS were considered. A replica estimated population was created using the National Centre for Social and Economic Modelling (NATSEM) microsimulation model of the Australian tax and transfer system (STINMOD+). Using a budget impact analysis approach, we modelled the effect on PPMS costs of an effective hypothetical disease-modifying treatment (DMT) that delays disease progression by a year from mild to moderate and a further year from moderate to severe PPMS. Results: An estimated 31, 650 Australians have multiple sclerosis (MS) including 4, 430 with PPMS. The proportion with PPMS was estimated to increase with age and disease severity. Overall 25% of males with MS, and 10% of females, were estimated to have PPMS. Societal cost of PPMS in Australia in 2018 was estimated at AU418.1 million. Indirect costs contributed 67.5% of total costs, attributable to reduced workforce participation and need for informal care. The modelled DMT was estimated to create savings of AU14.9 million (3.6%). Fewer people had moderate and severe PPMS resulting in major cost savings, partially offset by increased costs of treatment, care and support for a relative increase in the number of people with mild PPMS and their increased productivity losses. Limitations: Publicly available data may be incomplete. The potential cost of the DMT was not considered. Conclusions: The economic burden of PPMS was estimated at AU418 million in 2018. An effective DMT that delayed progression from disease severity states by one year could provide significant cost savings.